Comparison of three different media for freezing of epididymal sperm from the African buffalo (Syncerus caffer) and influence of equilibration time on the post-thaw sperm quality - F.C. Herold; K. De Haas; D. Cooper; B. Colenbrander; J.O. Nothling; W. Theunisen; B. Spillings; D. Gerber (Onderstepoort Journal of Veterinary Research, 2004)
Assisted reproductive techniques might prove themselves useful tools in producing buffaloes free of specific diseases (BFSD), which are in demand in South Africa. Freezing protocols for African buffalo semen must not only result in good post-thaw qualities, but must also be practical. Epididymal sperm from six mature African buffalo bulls was collected, diluted with three different semen extenders and frozen. Pre-freezing equilibration times between 2 and 9 h were tested. Total and progressive motility, longevity and acrosomal integrity were measured and compared. The use of TriladylTM proved to result in better post-thaw parameters than the other two diluents. Equilibration times of between 4 and 9 h did not influence post-thaw sperm qualities significantly. For some of the treatments, exposure to semen extenders before freezing for less than 4 h resulted in inferior post-thaw semen parameters.